Distribution of the planktonic foraminifer genus Streptochilus in Neogene sediments - Resig, Johanna M (Supplement to: Resig, JM (1989): Stratigraphic distribution of late Neogene species of the planktonic foraminifer Streptochilus in the Indo-Pacific. Micropaleontology, 35(1), 49-62, 1989)
Study of four species of the biserial planktonic foraminifer Streptochitus from Deep Sea Drilling Project cores of the Eauripik Rise, western equatorial Pacific, and Ninety-east Ridge, Indian Ocean, shows that both the stratigraphic distribution of species and their frequency patterns (though not actual frequencies or abundances) are correlative in the two areas, supporting their use as stratigraphic and paleoecologic index fossils. Their distributional trends are linked to eustatic sea level changes and to changes in the mixing of surface waters; low frequencies and species turnovers occur during regressive phases when strong circulation of oxygenated waters could lead to the subsequent decline of their oxygen-minimum habitat. The species S. subglobigerum. S. latum. S. globigerum, and S. globulosum succeed one another at intervals averaging 2,5 my from late middle Miocene Zone N15 through Quaternary Zone N23. The new species, Streptochilus suhglobigerum, is described for what was formerly thought to be a stratiraphically lower, disjunct part of the range of S. globigerum. These four species most likely belong to a single phylogenetic lineage as evidenced by some transitional morphologies.